DEVELOPMENT OF WORKSTATION FOR THE ROAD MASTER ON THE TRACK DISTANCE - Bieltiukov, V. P. (Science and Transport Progress, 2003)
The functions, task and the requirements showed to a subsystem, the automated workplace of the roadman of a distance of a way are determined in the article.